Statute of limitations under the penal law of Bulgaria - Girginov, Anton Tonev (Problems of legality, 2021)
Ukraine carries out intensive judicial cooperation in criminal matters with other European countries. A typical impediment to granting Ukrainian requests for such cooperation (e.g. extradition from another country, taking over Ukrainian criminal proceedings by the requested foreign country, recognition and enforcement of Ukrainian criminal judgments abroad) is the expiry of the time limitation period [lapse of time] not only under the Ukrainian law but also under the law of the foreign country that Ukraine requests for cooperation. The problem is that the criminal statute of limitations of most European countries is significantly different from the Ukrainian one. In view thereof, Ukrainian criminal lawyers are interested in having some general knowledge of the statute of limitations of other European countries, esp. such as Bulgaria. On the one hand, this foreign country has always been a steady partner of Ukraine in international judicial cooperation. On the other hand, the Bulgarian statute of limitations constitutes a good example of the different type of legal framework for lapse of time that requesting Ukrainian authorities shall necessarily consider. All penal laws of the contemporary Bulgarian state contained some statute of limitations. These laws are the 1896 Penal Law (repealed), the 1951 Penal Law upgraded to the 1956 Penal Code, after the full codification of this branch of law in Bulgaria (also repealed), and the existing Penal Code of 1968. The criminal statute of limitations outlines periods when competent state authorities have been inactive. The expiry of these periods (the lapse of time under law) extinguishes the immediate legal consequences of crimes or the punishments imposed by the court for them. In Bulgaria, the statute of limitations consists of substantive penal law provisions. This is a legislative recognition of its substantive nature. The concept that the criminal statute of limitation is a procedural legal institution has been overcome in Bulgarian theory, law and judicial practice. The statute of limitations produces procedural consequences also but they derive from its direct substantive law results as secondary effects. As in most other countries, the penal law of Bulgaria prescribes two types of limitation periods. The first one runs after the commission of the offence. It is also called ’limitation of the offence’; its expiry entails the extinction of the offender’s criminal liability preventing both the imposition of punishment on him/her and his/her conviction status as well. The second type of limitation period occurs after the imposition of an executable punishment. It is also called ’limitation of the punishment’; its expiry entails the extinction of the punishment imposed only. It does not eliminate the fact that the offender has been convicted. Under the Bulgarian Penal Code, each of the two types of statute of limitations includes not only general time limitations but also absolute ones as well. The former is applicable when the competent state authorities have not undertaken required activities whereas the latter applies only if the competent state authorities have failed to achieve a required result, namely: the imposition of punishment on the offender or the execution of his/her punishment.